PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN CD INTERAKTIF TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PAUL DI SMKN 1 LINTAU BUO - Danil Febri; Putra Jaya; Yasnidul Huda (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
The objective of this study is to determine the effect of using CD interactive media on learning outcomes. The problem in this research contents is about the low value of the average grade of 75.00 compared with KKM Ocular Measurement Using Electricity Lesson at SMK 1 Lintau Buo. It is influenced by the teaching methods, learning models, and instructional media. Therefore an interactive CD learning media been used as the treatment. This research uses one shot experiment study model as analytical approach. The subject of this research is students of class X TAV SMK 1 Lintau Buo. Data collected by giving a pre - test and post – test, in order to determine the effectiveness of the treatment. Data collection was conducted in four times lessons. The research instrument that had been used is subjective test as much as 20 questions divided into 5 questions for each lesson. Data were analyzed using SPSS 15 computer program. As the result, the average value of pre-test for the whole meeting is 50.95 while the average post-test score of 81.72, with the difference of the two is 30.78. In the percentage calculation, it has gained the result for 60.41 %. It can be concluded that there is a significant improvement in student learning outcomes after getting treatment using Interactive CD as an instructional mediaKeywords : Interactive CD , pre-test , post -test and Learning Outcomes